Voluntary socio-environmental disclosure practices in Brazilian agricultural cooperatives - Santana, Lorenna Gabriella Novaes; Santos, Jose Alexandre dos; Martinez, Marta Pagán; Moura-Leite, Rosamaria Cox (Revista de Administração da UFSM, 2018)
The objective of this article is to describe the voluntary disclosure of socio-environmental practices in Brazilian agricultural cooperatives. In order to reach the outlined objective, we analysed the annual reports on the websites of a non-probabilistic sample of the largest Brazilian agricultural cooperatives, referring to the period of 2015. For data analysis, the averages by subcategory and three indices of disclosure rate were used: Disclosure Index (DI), Business Disclosure Index (SDI) and General Business Disclosure Index (IGDE), General Index of Social Disclosure (IGDs). In addition, a fifth disclosure index was developed: the General Index of Environmental Disclosure (IGDa). The results obtained allow us to affirm that there is more disclosure of social information than environmental information, especially in relation to employees, concerns with the community and education, and that there is still a long way to go regarding good socio-environmental voluntary disclosure of agricultural and livestock cooperatives.